2012
DOI: 10.2478/v10298-012-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Reserve Utilization and Seedling Growth of Treated Seeds of Mountain Rye (Secale Montanum) as Affected by Drought Stress

Abstract: ABSTRACT.The environmental stress such as, drought are serious obstacles for field crops in further areas of the world, especially in arid and semiarid regions. In order to investigate drought stress on seed reserve utilization and seedling growth of treated seeds of mountain rye (Secale montanum), an experiment was carried out. Factorial experiment was carried out in completely randomized design with three replications. The first factor was the seed treatments (unpriming, hydropriming and osmopriming) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 13 publications
5
18
0
1
Order By: Relevance
“…To counteract the adverse effects of abiotic stress, seed priming methods have been applied to improve germination, uniformity, improve seedling establishment and stimulate vegetative growth in more field crops [30,31]. Wheat seeds were priming to increase germination characteristics and stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…To counteract the adverse effects of abiotic stress, seed priming methods have been applied to improve germination, uniformity, improve seedling establishment and stimulate vegetative growth in more field crops [30,31]. Wheat seeds were priming to increase germination characteristics and stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…This index is calculated as the sum of percent germination of seeds at 2 day intervals by the total germination period (Khan & Ungar, 1996). Timson's index is widely used and praised (Brown & Mayer, 1988;Ansari et al, 2012;Dwiyanti et al, 2014) while setbacks to Timson method have also been reported (Al-Mudaris, 1998). He reported with varying examples that different Timson germination indices could still be reached, adding levels of complications and interpretations (Al-Mudaris, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Germination is basic processes in the survival and success of a plant (Bradford, 2002;Ansari et al, 2012) and the ability to predict germination could enhance crop management. In fact, this distribution has been almost exclusively assumed so far in hydrothermal models (Gummerson, 1986;Bradford, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…The ability to predict the timing of germination of seeds and emergence of seedlings under a range of water regimes is useful for determining seeding date and subsequent seedling establishment success (Mesgaran et al, 2013;Garcia et al, 2013). Osmotic potential is a very important factor controlling seed germination, affecting both the rate and final percentage of germination (Ansari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%